Preparation and Characterization of Carboxymethyl Sago Waste and its Hydrogel - Lim, Jew Kiat (2006)
Carboxymethyl sago waste (CMSW) was prepared under heterogeneous condition as the product of the sago waste and sodium monochloroacetate (SMCA) in presence of sodium hydroxide (NaOH). The carboxymethylation of sago waste was optimized respect to degree of substitution (DS) and reaction efficiency (RE). Maximum values of DS and RE were obtained with aqueous isopropyl alcohol as the reaction medium. Data obtained also suggest that water: isopropyl alcohol with 1:15 ratio was most appropriate for the reaction. The concentration of aqueous sodium hydroxide solution, which is used to activate the cellulose and starch was found optimal at 25 % (w/v). The increase of concentration of SMCA leads to an increase of DS, but only in certain extent, approaching a maximum value with anhydroglucose unit of sago waste: SMCA with 1:2.1 in molar ratio. The highest value of DS is being obtained when carboxymethylation was performed at an hour of alkalization and 2 hours etherification at temperature of 55 oC. The values of DS and RE under optimum condition for CMSW were 1.06 and 61.1% respectively. Sago waste were fractionated into cold water soluble (2.8%), hot water soluble (7.5%), 5% sodium hydroxide soluble polysaccharides (starch and hemicelluloses) (78.1%), 10% acetic acid and sodium chlorite (3.1%), 24% potassium hydroxide and 2% boric acid soluble hemicelluloses (1.9%) and -cellulose (10.5%), respectively. Moisture content, density, values of pH and solubility in water of CMSW were found higher than sago waste and these properties were enhanced by increasing the DS of CMSW. Fourier Transform Infrared Spectroscopy (FTIR) of CMSW revealed two new bands with sharp intensity at 1320 and 1422 cm-1, which respectively correspond to the vibration of substituted carboxyl groups (COO). Scanning electron microscopy studies showed that the sago waste consists of surface morphologies of cellulose fibres and smooth surface and oval granules of starch. After carboxymethylation, CMSW were rough and grooved with agglomeration of cellulose fibres and starch granules. Thermogravimetric analysis and differential thermogravimetric of CMSW showed the thermal stability of CMSW was more stable than sago waste from 35 to 900 oC. Results from differential scanning calorimetric revealed that the carboxymethylation reduced the crystallinity of starch and cellulose and reduced the portion of starch granules being able to be gelatinized in CMSW. Viscometry capillary study indicates that the degradation of the sago waste chains was occurred where the intrinsic viscosity and molecular weight of CMSW were found to be decreased after carboxymethylation. The CMSW hydrogels with various parameter of cross-linking were prepared by using electron beam irradiation. CMSW hydrogel with DS of 1.06, 80 % of CMSW aqueous solution and irradiation dose of 40 kGy showed the highest of gel content. The swelling of CMSW hydrogel decreased with the increase of the dose of irradiation and CMSW concentration. The swelling of CMSW hydrogel in water increases with increasing of hydrophilic substituents (–CH2COONa) in CMSW hydrogel. Swelling ratio of CMSW hydrogel in alkaline medium (0.1 M NaOH) and sodium chloride (0.1 M NaCl) were lower than swelling in deionized water but higher than acidic medium (0.1 M HCl). The presence of cations in swelling medium were remarkably affected the swelling ratio of CMSW hydrogel.